MODEL PEMBELAJARAN EKSPOSITORY BERBANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA - Desak Nyoman Puspaeni (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2020)
SMP Negeri 2 Banjarangkan is a location for classroom action research. The purpose of writing this class action research is to find out whether the Expository learning model aided by Audio Visual media can improve student learning outcomes. This research was conducted at SMP Negeri 2 Banjarangkan in Class VIII.A where the ability of students for Indonesian subjects was low. Data collection method is a test of learning outcomes. The data analysis method is descriptive. The results obtained from this study are expository learning models assisted with audio visual media can improve student learning outcomes. This can be seen from the results obtained initially at 69.74 in the first cycle to 77.83 and in the second cycle to 82.17. The conclusion obtained from this study is that expository learning models assisted by Audio Visual media can improve the learning outcomes of Indonesian students in class VIII. Semester II of the 2018/2019 academic year at SMP Negeri 2 Banjarangkan.